PENGEMBANGAN KONSEP OUTCOME BASED EDUCATION BERBASIS 4 LITERASI BARU MATA KULIAH PENGEMBANGAN PEMBELAJARAN PKN SD - Maulana Siregar, Waliyul; Gandamana, Apiek; Rifai Harahap, Muhammad; Rahmania Putri, Suci; Edwina, Yosephine (Universitas Negeri Medan, 2024)
Abstract: The purpose of this study is to build a new paradigm of literacy-based OBE for the Elementary School Civics Learning Development course, FIP Unimed in the Elementary School Teacher Education Study Program. In the process of implementing the research, the Borg and Gall model was used, which includes planning, making an initial version of the product, initial field testing, revision of the main product, main field testing, revision of the operational product, revision of the final product, dissemination, and implementation. These are the research products that will be produced: 1) fulfillment of TKT 1 which focuses on the basics of the technology studied and reported (new literacy-based OBE concept); 2) fulfillment of TKT 2 which focuses on the formulation, concept, and/or application of the formulation (testing the new literacy-based OBE concept); and 3) obtain analytical and experimental analysis of the concept of function proof (new literacy-based OBE concept in lectures). Keyword: OBE, New Literacy, Development of Elementary School Civics Learning. Abstrak: Tujuan dari penelitian ini adalah untuk membangun paradigma baru OBE berbasis literasi baru untuk mata kuliah Pengembangan Pembelajaran PKn dalam Program Studi Pendidikan Guru Sekolah Dasar. Pelaksanaan penelitian menggunakan model Borg and Gall, mencakup studi pendahuluan, perencanaan, pembuatan awal produk, uji lapangan awal, revisi produk pengujian awal, uji lapangan utama, revisi produk utama, uji kelayakan, revisi produk akhir, diseminasi, dan implementasi. Produk penelitian yang akan dihasilkan: 1) pemenuhan TKT 1 yang berfokus pada dasar-dasar teknologi yang dikaji dan dilaporkan (konsep OBE berbasis literasi yang baru); 2) pemenuhan TKT 2 yang berfokus pada formulasi, konsep, dan/atau aplikasi formulasi (pengujian konsep OBE berbasis literasi yang baru); dan 3) memperoleh analisis analitis dan eksperimental konsep pembuktian fungsi (konsep OBE berbasis literasi baru dalam perkuliahan). Kata Kunci: OBE, Literasi Baru, Pengembangan Pembelajaran PKn SD.